NIEWERBALNE SPOSOBY NARUSZENIA CZCI W PRAWIE RZYMSKIM - Nowicka, Dobromiła (Zeszyty Prawnicze, 2016)
Non-verbal Acts Damaging Reputation in Roman Law Summary The aim of this article is to present the non-verbal types of conduct which damaged another person’s reputation under Roman Law. The author examines only those types of offensive conduct which did not involve physical assault on an individual’s bodily integrity. The article analyses abusive conduct subject to the edictum de adtemptata pudicitia, the first regulation on this matter; and secondly conduct penalised under the edictum ne quid infamandi causa fiat. The latter edict marked the peak in the legislation providing protection against all kinds of vilifying behaviour. The latter edict is discussed on the basis of passages from Ulpian with examples of its application.<br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;" />